(Research on effectiveness of Production of Palm Oil Biodiesel using Static-Mixer Reactor) - Rizal Alamsyah; Lukman Junaidi; Enny Hawani Lubis (Warta Industri Hasil Pertanian, 2010)
Research on Effectivenes of Production of Palm Oil Biodiesel Using Static-Mixer Reactor has been conducted. The aim of research was to evaluate the faster and more effective of production process of biodiesel compare to the existing conventional mehod using blade-agitator. The production method investigated was related to application of Static-Mixer Reactor in the biodiesel production. The results show that application of Static-Mixer Reactor ij the biodiesel production give the faster trans-esterification reaction speed in producing Fatty Acid Methyl Ester/FAME compare to blade-agitator reactor. To produce FAME 96,5% as required in SNI Biodiesel (SNI 04-7182-2006), Static-Mixer Reactor only needs 15, 10, dan 5 minutes for temperature 50, 69 and 70 C .  while blade-Mixer Reactor also could produce biodiesel with the viscosity and acid value better than biodiesel which produced by blade-agiitator reactor. The resultd also show that application of static mixer could produce biodiesel that meet the requirements of Indonesia Nasional Standar for Biodiesel (SNI) 04-7182-2006. These could be seen in the quality parameters related to acid value, glycerol total, viscocity, water content, and density.